Municipal Street Management in the United States - Stidger, Ruth W (2025)
Financing, traffic congestion, and the use of new communication technology are the main challenges for the future of municipal authorities. In the state of California, USA, as in other states across the country, there has been a reduction in the funds available for roads. For example, in the San Francisco Bay Area, the budget for roads was reduced by $2.6 billion, approximately 22.6%. This reduction originated from a recent decrease in taxes, which was implemented to combat the economic recession affecting the country, and has forced municipal governments to find more efficient ways to invest the money allocated for road maintenance and preservation.